2020
DOI: 10.1021/acs.est.0c04776
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characteristics and Driving Factors of Black Carbon in Augsburg, Germany: Combination of Mobile Monitoring and Street View Images

Abstract: The study investigates the spatial pattern of black carbon (BC) at a high spatial resolution in Augsburg, Germany. Sixty two walks were performed to assess the concentrations of equivalent black carbon (eBC), ultraviolet particulate matter (UVPM), and equivalent brown carbon (eBrC) in different seasons and at different times of the day with a mobile platform (i.e., trolley). Along with BC measurements, images of street microenvironments were recorded. Meteorological parameters, including temperature, relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 53 publications
0
29
1
Order By: Relevance
“…To evaluate the relative performance of MA200, this study was analyzed BC data collected from multiple MA200 devices, identified individually by serial numbers (MA200-0051, MA200-0053, MA200-0059, MA200-0060, MA200-0155, MA200-0153, MA200-159) and used the MA200's onboard signal-processing to moderately reduce the noise of the BC signal. Comparative measurements of the microAeth® MA200 115 and a stationary Aethalometer (AE33, Magee Scientific, Berkeley, USA) showed good agreement of stationary measurements carried out between the individual walks (Liu et al, 2020b). Information about the date, duration, and time resolution (time base) of each MA200 device as used during measurement for this study are summarized in Table 1.…”
Section: Instrumentationmentioning
confidence: 87%
“…To evaluate the relative performance of MA200, this study was analyzed BC data collected from multiple MA200 devices, identified individually by serial numbers (MA200-0051, MA200-0053, MA200-0059, MA200-0060, MA200-0155, MA200-0153, MA200-159) and used the MA200's onboard signal-processing to moderately reduce the noise of the BC signal. Comparative measurements of the microAeth® MA200 115 and a stationary Aethalometer (AE33, Magee Scientific, Berkeley, USA) showed good agreement of stationary measurements carried out between the individual walks (Liu et al, 2020b). Information about the date, duration, and time resolution (time base) of each MA200 device as used during measurement for this study are summarized in Table 1.…”
Section: Instrumentationmentioning
confidence: 87%
“…S1). Meanwhile, as performed in our previous study (Liu et al, 2021), we divided the monitoring route into four microenvironment groups in Augsburg, including high traffic flow (H_Traffic, average 500-1000 vehicles per hour), medium traffic flow (M_Traffic, average 200-500 vehicles per hour), low traffic flow (L_Traffic, average 1-200 vehicles per hour), and park area (N_Traffic, average 0 vehicles per hour), according to the actual traffic density examined during the daytime and determined from the traffic flow observed by street views.…”
Section: Study Design and Routesmentioning
confidence: 92%
“…Comparative measurements of the MA200 and a stationary Aethalometer (AE33, Magee Scientific, Berkeley, USA) taken approximately 30 to 60 min between walks showed a good agreement (Pearson's r = 0.933) (Liu et al, 2021). In addition, it is worth noting that when the AE33 was used for monitoring black carbon at the same time as the MA200, the AE33 was placed in a fixed station, while the MA200 was used outdoors (in the stroller) during the individual walks, which may have presented different relative humidity and temperature values.…”
Section: Preparation Of the Instrumentsmentioning
confidence: 94%
See 2 more Smart Citations